MINAT MAHASISWA MENGGUNAKAN SOFTWARE ACCOUNTING: EFEK DARI COMPUTER ANXIETY DAN COMPUTER ATTITUDE - Amirudin, Salsabila Ratna Dilla; Suhartini, Dwi (APSSAI, 2021)
The aim of this study was to examine the effect of computer anxiety and computer attitude towards accounting students' desires in using accounting software. Through a quantitative approach, this study uses the PLS statistical test tool to test the hypothesis. Primary data sources were obtained through direct distribution of questionnaires and the results were obtained that as many as 98 students had filled out the questionnaires. While the sampling design was carried out by random sampling, samples size was determined by the Slovin formula. The results showed that computer anxiety and computer attitude influenced students' desire to use accounting software. Students have been able to overcome their worries with their enthusiasm to continue to learn to use accounting software and make changes to the behavior of a generation of credible accountants who are able to face the era of the industrial revolution 4.0.